Gambaran Tingkat Pengetahuan Bantuan Hidup Dasar (BHD) Tenaga Kesehatan di Puskesmas Lhoksukon - Anna Millizia; Adi Rizka; Tata Azzalia Khairan (Lembaga Pengembangan Kinerja Dosen, 2026)
Indonesia ranks 36th among countries most prone to natural disasters, with 216 earthquakes recorded by BNPB between 2009 and 2019. Aceh is one of the high-risk regions, having experienced major disasters such as floods, earthquakes, and the 2004 tsunami. These conditions highlight the importance of knowledge of basic life support (BLS), which is essential for managing respiratory arrest, cardiac arrest, and airway obstruction in emergency situations. This study aimed to determine the level of basic life support knowledge among health workers at the North Lhoksukon Health Center, Aceh. A descriptive observational method with a survey approach was used to provide a general overview of respondents’ characteristics. The study applied univariate analysis and involved a total sample of 139 health workers. The results showed that most respondents had a good level of knowledge (116 people; 83.5%), followed by sufficient knowledge (13 people; 9.4%) and poor knowledge (10 people; 7.2%). These findings indicate that while the majority of health workers demonstrate good understanding, there is still a need for improvement among those in the sufficient and poor categories. Therefore, it is recommended that institutions provide regular BLS training to maintain and enhance the knowledge of health workers.